Analisis Hubungan Status Gizi Lansia Di Puskesmas Limboto Barat - Hatta, Herman; Pakaya, Ririn; Laiya, Marlina (Gorontalo Journal of Public Health, 2018)
Nutritional problem have been found in the elderly which can be inform of lack of nutrient intake. The research aimed to find out thefactors related with the nutrient status of the elderly, the study wasthe quantitative research which was also naturally an analyticalresearch with the cross sectional study approach. The sample of theresearch was as many as 121 respondents which were determined byusing the purposive sampling technique. The finding of the researchfrom 121 respondents was showing that there was 9 elderly with theundernutrition status (7,4%) while there were 69 (57,0%) of them are innormal nutriention status. In addition, there were 43 of them (35,5%)was overnutrition. Based on the analysis bivariate by using thefisher’s exact test was showing that there was no relationship betweenthe physical activity with the nutrientional status in the elderly withthe value ρ = value 0,056 > ɑ 0,05, there was also no relationshipbetween income with the nutrientional status on elderly with the valueof ρ = value 0,001 > ɑ 0,05. However, there was a relationshipbetween the education with the nutrientional status on elderly with thevalue of ρ = value 0,003 > ɑ 0,05.